2018
DOI: 10.1038/s41598-018-35752-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative coffee consumption on gastrointestinal function after abdominal surgery: A systematic review and meta-analysis of randomized controlled trials

Abstract: Coffee is believed to prevent postoperative ileus. This systematic review and meta-analysis was undertaken to determine the effectiveness of coffee consumption in stimulating gastrointestinal function after abdominal surgery. A number of databases for randomized controlled trials comparing coffee consumption following abdominal surgery versus water drinking or no intervention were searched. Cochrane’s Risk of Bias tool was used to assess risk of bias in included studies. Six trials involving 601 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
(40 reference statements)
1
16
0
6
Order By: Relevance
“…Coffee was assessed in three RCTs and showed a significant effect on the reduction of the duration of GI function impairment. This is interesting while it was shown that it also reduced these outcomes outside the ERP 68 . The caffeine was supposed to reduce inflammation in the bowel by stimulating the vagal pathway 69 .…”
Section: Discussionmentioning
confidence: 81%
“…Coffee was assessed in three RCTs and showed a significant effect on the reduction of the duration of GI function impairment. This is interesting while it was shown that it also reduced these outcomes outside the ERP 68 . The caffeine was supposed to reduce inflammation in the bowel by stimulating the vagal pathway 69 .…”
Section: Discussionmentioning
confidence: 81%
“…In a review study by Eamudomkarn et al, it was reported that coffee consumption as a beverage in the postoperative phase causes earlier bowel movements and shorter duration of first flatulence [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literatürden altı randomize kontrollü çalışmanın dahil edildiği [26][27][28][29]31,32 bir sistematik derleme ve meta-analiz çalışmasında ise kahve tüketiminin kolorektal ve jinekolojik cerrahi sonrası ilk defekasyon süresini azalttığı ancak sezaryen üzerinde etkili olmadığı bildirilmektedir 37 . Yapılan sistematik derleme ve meta-analizlerde çalışmaların bias riskinin orta ve yüksek olması nedeniyle kahve tüketiminin ileus üzerine etkisine yönelik kanıt düzeyinin düşük ve orta düzey olduğu belirtilmiştir 37,38 .…”
Section: Kahve Tüketimiunclassified
“…Kahve tüketimi kolay tolere edilmesi, ucuz olması, kolay bulunabilmesi ve uygulanabilmesi nedeniyle önerilmektedir. Yapılan çalışmalarda kahve tüketiminin olumsuz etkisi bildirilmemiş olup olumlu etkileri nedeniyle ameliyat sonrası dönemde tüketimi önerilmektedir 29,36,38 . Ancak konuyla ilgili yapılan çalışmalarda, hastaların kahve/kafein tüketim miktarının standart olmaması, hastaların ilave analjezik ve antiemetik gereksinimleri gibi parametrelerin değerlendirilmemesi gibi bazı sınırlılıklar yer almaktadır.…”
Section: Kahve Tüketimiunclassified